2020
DOI: 10.1167/iovs.61.2.32
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Evolution and Remodeling of Soft Drusen in Rhesus Macaques

Abstract: PURPOSE.To characterize the evolution and structure of soft drusen in aged rhesus macaques using in vivo multimodal retinal imaging and ex vivo histologic and ultrastructural analyses as a nonhuman primate model of early age-related macular degeneration (AMD). METHODS.Multimodal imaging including fundus photography, spectral domain optical coherence tomography (SD-OCT), and fundus autofluorescence (FAF) were used to characterize and track individual drusen lesions in 20 aged rhesus macaques (mean age 23.3 ± 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 81 publications
(118 reference statements)
1
20
0
Order By: Relevance
“…45,54,76 Some mouse strains exhibit thin BLamD, and, to date, only models involving the genes listed above have thick BLamD. 66,77 Aged monkeys may naturally exhibit soft drusen, but lack BLamD and do not progress to atrophy or NV, 78 suggesting that BLamD is required for drusen that progress. Indeed, BLamD may share some of the pathophysiology postulated for drusen, with important differences.…”
Section: Discussionmentioning
confidence: 99%
“…45,54,76 Some mouse strains exhibit thin BLamD, and, to date, only models involving the genes listed above have thick BLamD. 66,77 Aged monkeys may naturally exhibit soft drusen, but lack BLamD and do not progress to atrophy or NV, 78 suggesting that BLamD is required for drusen that progress. Indeed, BLamD may share some of the pathophysiology postulated for drusen, with important differences.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are also consistent with studies using SD-OCT imaging, in which soft drusen in macaques demonstrate homogenous internal reflectivity, whereas those in humans exhibit greater heterogeneity in reflectivity with variable internal substructures. 8,58,59 Thus our data suggests both localized and global impact on lipofuscin distribution in eyes with drusen and AMD in primate species. As the pathogenesis of AMD is complex and multifactorial, including oxidative stress, 60 lipid accumulation, 61,62 immune dysregulation, 63,64 and vascular changes, 65,66 the role of lipofuscin accumulation among these factors remains unclear.…”
Section: Discussionmentioning
confidence: 54%
“…In our study, we found a subset of eyes with these punctate lesions, which exhibited similar qAF8 levels to age-matched eyes without fundus findings, and supports our hypothesis that lipoidal degeneration is not related to soft drusen or AMD. 8 NHPs are potentially important animal models of AMD because they possess a true macula similar to humans and spontaneously develop soft drusen that has similar components and ultrastructure 67 and share similar genetic susceptibility loci. [68][69][70] However, despite reported drusen prevalence of up to 47% in some colonies, [5][6][7]71 macaques do not develop advanced, atrophic AMD, or risk features for atrophy, such as reticular pseudodrusen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SD-OCT was performed using a 20 º x 20º volume scan and a 30 º x 5º raster scan protocol, centered on the fovea and in areas of chorioretinal colobomas, with progression mode using retinal vessel tracking enabled where possible to reliably image the same area for longitudinal imaging sessions. All retinal measurements were made using the Heidelberg Explorer software (version 1.9.13.0, Heidelberg Engineering, Heidelberg, Germany), which has been used in prior studies and calibrated for both humans (54)(55)(56) and macaques (57)(58)(59).…”
Section: Multimodal Ocular Imaging and Analysismentioning
confidence: 99%